PENELUSURAN KEARIFAN LOKAL MASYARAKAT DESA TENGGULI KECAMATAN SAJAD DALAM E-POCKET BOOK CUKA RAMBUTAN - Lisna Yani; Hairida Masriani; Masriani Masriani (Universitas Tanjungpura, 2019)
AbstractThe aim of this research was to find out how to make rambutan vinegar by the people of Tengguli Village, Sajad District. The form of this research is descriptive research. The location taking technique in this research used purposive sampling technique while the sampling technique in this research used snowballing sampling technique. The data collection tool carried out in this research is the interview guideline sheet and the material used is in the form of stationery. Based on the results of interviews with the people of Tengguli Village, Sajad Regency, it is known that the people of Tengguli Village made rambutan vinegar through a traditional fermentation process using yeast (Saccharomyces cerevisiae) and without using yeast. From the results of the research it can be concluded that there are 2 ways of making rambutan fruit vinegar by the people of Tengguli Village, Sajad District namely fermentation using yeast (Saccharomyces cerevisiae) and without using yeast. Keywords: Fermentation, Local Wisdom, Rambutan Vinegar.